Earnings losses and the role of the welfare state during the COVID-19 pandemic: Evidence from Sweden - Adrian Adermon; Lisa Laun; Patrik Lind; Martin Olsson; Jan Sauermann; Anna Sjögren (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2022)
Many governments introduced temporary adjustments to counter the economic and health consequences of the COVID-19 pandemic. We study the importance of already existing government transfers and pandemic measures to mitigate individual income losses during the pandemic in Sweden using a difference-in-differences approach and population-wide data on monthly earnings and government transfer payments. We find that labor earnings dropped by 2.7 percent in 2020. Existing transfers and pandemic measures reduced earnings losses to 1.5 percent. These average effects mask considerable differences in income losses, which were, by and large, evened out by existing transfers and pandemic measures.
Keywords: D31; E24; H20; H12; C23; 330; COVID-19; income inequality; government transfers; short-time work